Baseline Stroke Severity as a Predictor of 30-Day Post-Ischemic Stroke Disability Outcome - Diana Teresa; Rizaldy Taslim Pinzon; Sugianto Adisaputro (Fakultas Kedokteran Universitas Brawijaya, 2022)
More than 50% of patients who survived stroke have a chronic disability. The National Institute of Health Stroke Scale (NIHSS) is a scoring system to determine the neurologic deficit of a stroke patient. This study analyzed stroke severity based on baseline NIHSS score as a determinant for 30-day post-ischemic stroke disability. This study method uses a retrospective cohort design based on medical records and stroke registry of ischemic stroke patients in Bethesda Hospital Yogyakarta. During admission, the predictive factors for the disability of the study subjects were evaluated. The baseline NIHSS assessment score was measured at 1x24 hours after admission. Disability was measured using a simplified modified Rankin Scale questionnaire (smRSq) Indonesian version at 30-day post-ischemic stroke. Statistical analysis includes univariate, bivariate, and logistic regression multivariate data analysis. The subjects were 84 patients with ischemic stroke. Disability at 30-day post-ischemic stroke occurred in 22 patients (26.2%). Logistic regression multivariate analysis show that Neutrophil to Lymphocyte Ratio (NLR) (RR: 4.488, CI: 1.873–10.756, p: 0.001) and baseline NIHSS score (RR: 28.563, CI: 2.891–282.181, p: 0.004) together significantly affect the mRS of 30-day post-ischemic stroke. Patients admitted with a higher baseline NIHSS score have a 28.5 fold risk for a worse functional outcome than those with lower baseline NIHSS scores. Stroke severity based on baseline NIHSS score is a determinant factor for disability in patients at 30-day post-ischemic stroke.